Maleimides in recent sediments – Using chlorophyll degradation products for alaeoenvironmental reconstructions - Naeher, Sebastian; Schaeffer, P.; Adam, P.; Schubert, C. (Pergamon-Elsevier Science Ltd, 2013)
Maleimides (transformation products of chlorophylls and bacteriochlorophylls) were studied in recent sediments from the Swiss lake Rotsee and the Romanian Black Sea Shelf to investigate chlorophyll degradation, the role of oxygen inmaleimide formation, and to identify their sources. Naturally occurring maleimides (i.e. “free” maleimides) and maleimides obtained after chromic acid oxidationof sediment extracts (i.e. “bound” maleimides) were analysed. 2-Methyl-maleimide (Me,H maleimide), 2,3-dimethyl-maleimide (Me,Me maleimide), 2-methyl-3-vinyl-maleimide (Me,vinyl maleimide), 2-methyl-3-ethyl-maleimide (Me,Etmaleimide) and traces of 2-methyl-3-iso-butyl-maleimide (Me,i-Bu maleimide) occurred naturally in the sediment with a large predominance of the Me,Et homologue. Tetrapyrrolic pigments related to chlorophylls were the main source of maleimides, although variable contributions of other sources such as cytochromes and/or phycobilins cannot be completely ruled out.The predominantMe,Et maleimide and Me,vinylmaleimide most likely originate mainly from chlorophyll a related pigments. The same holds forMe,Hmaleimide,which might be formed following degradation of ring E from the tetrapyrrolic nucleus.Alternatively,Me,Hmaleimide and Me, Memaleimides might be formed by a recently discovered transformation pathway involving the oxidation of vinylic chlorophyll substituents and the formation of an aldehyde intermediate. 2-Methyl-3-n-propyl-maleimide (Me,n-Pr maleimide) and Me,i-Bumaleimide arising from bacteriochlorophyllrelated pigments traced the presence of phototrophic sulfur bacteria (Chlorobi), indicating photic zone euxinic and anoxic conditions inRotsee during the last 150 years and throughout the Black Sea history, including the limnic phase of theBlack Sea (Unit 3). Some other minor maleimides with specific alkylation pattern also originate from bacteriochlorophylls, while the source of others could not be identified. Freemaleimides weremainly formed in the sediment in the absence of oxygen. Novel maleimide degradation indices are proposed to estimate the degree ofOMdegradation (OM freshness/degradability). These proxies are applicable on longer timescales than e.g. the chlorin index.